Cost-utility analysis of memantine in Alzheimer’s Disease in Brazil (Research, Society and Development, 2022)
Accelerated population aging has led to a progressive increase in dementia, particularly Alzheimer’s Disease (AD).   The study’s objective was to perform a cost-utility analysis on the use of memantine in the severe stage of AD in Brazil compared to no specific pharmacological treatment from the perspective of the Brazilian Unified Health System (SUS). A Markov model was designed to simulate the progression of AD through five finite stages of health that considered cognitive function and a time horizon of five years. Progression probabilities were derived from clinical trials and population-based studies. Direct costs included hospitalization, medical consultation, use of additional medications, as well as laboratory tests. The measures for Quality Adjusted Life Year (QALY) were derived from the international literature. Costs and benefits were discounted by 5%. Compared to no specific pharmacological treatment, memantine was associated with gains in QALY and additional costs. The model showed that memantine resulted in a gain of 0.00308 QALY over the simulated 5 years and an increase in costs of R$351.50 per patient in already discounted values, resulting in an incremental cost-effectiveness ratio (ICER) of R$114,123.38 per QALY. The cost and effect of memantine on AD progression were the variables under the most uncertainty. Although memantine represents gains in QALY, its ICER is considered high for the Brazilian context considering its high costs and its small and limited benefit in time.